L’hybridation des savoirs pour travailler (sur) le paysage en éducation au développement durable - David Bédouret; Christine Vergnolle Mainar; Raphaël Chalmeau; Marie-Pierre Julien; Jean-Yves Léna (Projets de Paysage)
Current expectations in education for sustainable development imply raising students’ awareness of the social issues discussed in their region and to help them reflect on the potential futures of that region. The landscape is a relevant lever for children because it allows an approach involving feelings, thus helping them address the complexity of the issues involved. This results in renewed use of the landscape in education. From this perspective an experiment conducted in a primary school based on current observations led the students to explore past changes thus enabling them to more effectively project into the future. The students came into contact with different forms of knowledge (scientific and vernacular knowledge linked to the experiences of local actors) which they progressively aggregated to their existing knowledge sets through emotional maps. The study of these maps show that the students hybridised their existing knowledge sets by interconnecting them, thus producing new knowledge sets enabling them to reflect on the future.